Peran E-Commerce dalam Meningkatkan Akses Pasar Industri UMKM - M Romadhoni Adi Setiawan; Muhammad Yasin (Universitas 45 Surabaya, 2026)
The rapid advancement of digital technology has encouraged many micro, small, and medium enterprises (MSMEs) to adopt e-commerce as a strategic platform for marketing and selling their products. This study examines the role of e-commerce in expanding market opportunities for MSMEs, particularly within the industrial sector. Through the use of digital platforms, MSMEs are able to reach consumers across broader geographic areas that were previously difficult to access, thereby increasing market penetration and business exposure. In addition, e-commerce enhances product visibility, enables more efficient promotional activities, and simplifies transaction processes through integrated digital systems. The findings indicate that e-commerce has become a crucial factor in supporting MSMEs to expand their market reach, improve competitiveness, and adapt to changing consumer behavior in the modern economy. Furthermore, digital marketing and online sales channels help MSMEs maintain business sustainability by reducing operational costs and increasing flexibility in responding to market demand. Therefore, the adoption of e-commerce can be considered an effective strategy to support MSME development and contribute positively to regional economic growth in an increasingly digitalized business environment.